Volatile aroma compounds in Citrus hystrix oil - Omar, Muhammad Nor (Malaysian Agricultural Research and Development Institute, 1999)
The essential oil of Citrus hystrix was prepared from fresh leaves and peels and analysed by means of capillary GC and GC-MS. Forty-one components were identified, accounting ca. 95% of the oil, depending on the method of preparation. The leaf oil contains l-citronellal (61.73%) as a major compound whereas l-limonene, sabinene and a-pinene are predominant in the peel oil. This is th.e first time p-menthan-8-ol (dihydro-a-terpineol), guaiol, and 4-p-menthene is reported in C. hystrix oil.